PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN PENALARAN DAN BERPIKIR KRITIS PADA SISWA MTs NEGERI 3 LANGKAT - Muhammad Arif Hidayat (Tazkiya: Jurnal Pendidikan Islam, 2021)
The ability to think critically Jurisprudence of students who learn with problem-based learning models is better than the ability of students who study normally. Increased critical thinking skills Jurisprudence of students who learn with problembased learning models is better than the ability of students who study normally. The ability of reasoning Jurisprudence of students who learn with problem-based learning models is better than the ability of students who study normally. Improving the ability of reasoning Jurisprudence of students who learn with problem-based learning models is better than the ability of students who study normally. The attitude of students towards learning problem based learning models as well as questions of critical thinking and reasoning that is given is very positive. This learning makes students feel happy, interested, challenged, and can foster mutual respect and courage in communication. The teacher has a positive view of Jurisprudence with a problem based learning model. The teacher believes that this learning has the opportunity to be applied. However, the implementation requires optimal teacher preparation, especially in designing teaching materials in the form of student worksheets and the ability of heterogeneous group members, so that in each group there are students who can help other students. Keyword : Ability, Problem Based Learning, Reasoning, Critical Thinking